2018
DOI: 10.1371/journal.pone.0203035
|View full text |Cite
|
Sign up to set email alerts
|

Silodosin versus tamsulosin for medical expulsive treatment of ureteral stones: A systematic review and meta-analysis

Abstract: Silodosin, a recently introduced selective α-blocker, has a much higher selectivity for the α-1A receptor. The efficacy and safety of silodosin compared to tamsulosin in medical expulsive therapy (MET) are controversial. The objective of this study was to assess the efficacy and safety of silodosin compared to tamsulosin for treating ureteral stones <10 mm in diameter. We systematically searched the PubMed, EMBASE, Cochrane library, and Scopus databases from their inception to May 2018. We included randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
3
17
1
1
Order By: Relevance
“…Shockwave lithotripsy and surgical procedures like URSL are not free of complication, thus, alternative conservative methods have been applied especially when stones are located in distal ureter and are less than 10 mm. Multiple drugs such as α-blockers (tamsulosin, silodosin, alfuzosin and naftopidil), [7][8][9] nifedipine (calcium channel blockers (CCBs)) 10 and phosphodiesterase inhibitors (PDEI) (sildenafil 11 and tadalafil 12 ) have been found to be effective in facilitating ureter stones compared with general measures such as use of non-steroidal inflammatory drugs (NSAIDS), hydration, antispasmodics, diuretics and placebo. Of these drugs tamsulosin has been widely studied and has been found to facilitate stone expulsion not only in distal but also other parts of ureter.…”
Section: Introductionmentioning
confidence: 99%
“…Shockwave lithotripsy and surgical procedures like URSL are not free of complication, thus, alternative conservative methods have been applied especially when stones are located in distal ureter and are less than 10 mm. Multiple drugs such as α-blockers (tamsulosin, silodosin, alfuzosin and naftopidil), [7][8][9] nifedipine (calcium channel blockers (CCBs)) 10 and phosphodiesterase inhibitors (PDEI) (sildenafil 11 and tadalafil 12 ) have been found to be effective in facilitating ureter stones compared with general measures such as use of non-steroidal inflammatory drugs (NSAIDS), hydration, antispasmodics, diuretics and placebo. Of these drugs tamsulosin has been widely studied and has been found to facilitate stone expulsion not only in distal but also other parts of ureter.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge this retrospective study appears to be the first aiming to compare the effects of tamsulosin 0.4 mg with silodosin 4 mg and 8 mg as medical expulsive treatment after SWL. A recent meta-analysis showed that all the previous published studies compared tamsulosin 0.4 mg with silodosin 8 mg, revealing higher expulsion rates for silodosin 8 mg, none of them evaluating the effect of lower dose silodosin [ 11 ]. Although controversies exist, α-blocker therapy is recommended by the European Association of Urology Guidelines as medical expulsive treatment, especially for distal ureteric stones, facilitating the stone passage due to the relaxation of the smooth muscle of the ureter [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, these patients had fewer incidences of pain episodes (pooled MD: −0.3, 95% CI: −0.51, −0.09) compared with those receiving tamsulosin. 122 Ozsoy et al 123 compared the efficacy of silodosin with tamsulosin in a pooled data of 409 patients. The meta-analysis results favored • The mean change in the IPSS QoL index score at 3 months in the naftopidil, tamsulosin, and silodosin groups was +1.3, +1.4, and +0.9, respectively…”
Section: Limitations Future Implications For Research and Clinical Pr...mentioning
confidence: 99%